2016
DOI: 10.1159/000454797
|View full text |Cite|
|
Sign up to set email alerts
|

Comparison of Dolphins' Body and Brain Measurements with Four Other Groups of Cetaceans Reveals Great Diversity

Abstract: We compared mature dolphins with 4 other groupings of mature cetaceans. With a large data set, we found great brain diversity among 5 different taxonomic groupings. The dolphins in our data set ranged in body mass from about 40 to 6,750 kg and in brain mass from 0.4 to 9.3 kg. Dolphin body length ranged from 1.3 to 7.6 m. In our combined data set from the 4 other groups of cetaceans, body mass ranged from about 20 to 120,000 kg and brain mass from about 0.2 to 9.2 kg, while body length varied from 1.21 to 26.8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
100
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(111 citation statements)
references
References 65 publications
6
100
2
Order By: Relevance
“…; Ridgway et al. ), and descriptions of monodontid arterial retia and related vasculature (Vogl & Fisher, ,b, ). Previous cranial endocast descriptions are of particular interest because the most detailed relevant data comprise the sister clade to monodontids, the true porpoises or phocoenids (Racicot & Colbert, ; Racicot & Rowe, ), and a successive sister taxon, a delphinid Tursiops truncatus (Colbert et al.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…; Ridgway et al. ), and descriptions of monodontid arterial retia and related vasculature (Vogl & Fisher, ,b, ). Previous cranial endocast descriptions are of particular interest because the most detailed relevant data comprise the sister clade to monodontids, the true porpoises or phocoenids (Racicot & Colbert, ; Racicot & Rowe, ), and a successive sister taxon, a delphinid Tursiops truncatus (Colbert et al.…”
Section: Resultsmentioning
confidence: 99%
“…; Ridgway et al. ), in the case of fossils it is difficult to separate brain mass entirely from other aspects of the endocranial space. Endocranial volumes and other measurements from extant specimens, with comparisons with actual brain volumes, can inform estimates for fossil specimens, making broader comparisons more tenable.…”
Section: Introductionmentioning
confidence: 99%
“…Table 1. The above image highlights the current available statistics for the cerebral cortex of cognitive sophisticated terrestrial mammal species as well as several species of cetaceans (see [2,3,12,13,17,29,30,48,53,67,70,[77][78][79][80][81][82][83][84][85]). The table on top of the figure provides estimations of different physiological parameter for the brains of great apes, humans, and African elephants.…”
Section: The Primary Role Of Connectivity In Intelligencementioning
confidence: 99%
“…Furthermore, one of the most fascinating characteristics of their brains is the high degree of cortical gyrification and the resulting neocortical surface area. Therefore, in spite of the fact that recent studies have revealed great diversity amongst the brains found across this order (e.g., differences in brain parts, as well as body and brain measurements) [6,29], based on available data it is plausible to argue that, generally speaking, their brains appear to have followed the second pathway (Route 2), presented by the mathematical model being used to support the hypothesis exploring how brains evolved naturally and the causes of increased cognitive capacities. More specifically, if the assumption being made is that the depth of the information-processing hierarchy in the cerebral cortex of cetaceans is lower when compared to most of the intelligent terrestrial mammals species, then those defending complex cognition in cetaceans would need to demonstrate the existence of a higher neural connectivity (and thus higher metabolic costs), but, at the same time, a comparable (or higher) number of neurons in their cortices when compared to terrestrial mammal species for which there is enough documented evidence (besides humans) for their overall cognitive superiority, for example the great apes.…”
Section: Implications For Cetacean Cognitionmentioning
confidence: 99%
See 1 more Smart Citation